Green Supply Chain Management Practice in the Banking Sector: A Literature Review - Amrita Nandy; Mohammad Mamun Habib (ExcelingTech, 2023)
Reviewing the state-of-the-art literature, the authors in this paper have demonstrated how various tactics of Green Supply Chain Management are being practiced in Bangladesh and the prospects of such strategic implication on the banking sector. This paper is based on the secondary data, particularly selected articles published in various online databases from the year 2011 to the year 2023. The study shed lights on many innovative measures of digitalization, while a gap has been spotted between the existing policies and practices. Thus, being a highly systematic and structural business, banks in Bangladesh are yet struggling to adopt a unified green supply chain model to ensure overall green construction. Additionally, the findings may benefit policy makers and managers to formulate strategic decisions regarding the value implying various techniques of greening throughout the supply chain. A conclusion has drawn with the scope of the potential research opportunities to attain a sustainable supply chain which will accelerate the economic inclusion of the economy.